American "Lawrence of Arabia" Dies (The Biblical archaeology review, 1976)
Wendell Phillips, dead at the age of 54, was surely the world’s richest archaeologist. The "riches" part of his rags-to-riches story resulted from hundred of oil leases which gave him the right to extract and sell the black gold. At his death, he was the largest individual holder of oil concessions in the world. […]